EFFECT EXPLICIT METHOD INSTRUCTION HEALTH EDUCATION SPRAIN ON FIRST AID UKM FUTSAL IN STIKES HUTAMA ABDI HUSADA TULUNGAGUNG - Suciati Suciati; Purnomo Purnomo; Surtini Surtini; Pindi Yuli Antika (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2020)
Sprain most often occurs in a various sport, futsal is one sport that often causes injury, that is sprain. Sprain injuries will get the worse if not done first aids correctly.  Sprain can occur due to excessive physical stress, sudden or repeated overuse of joints, sepecially in futsal athletes injury that is the tearing of the ligament (tissue that connects bones to bones) or joint capsule that causes instability in the joint. Clinical manifestations include pain, inflammation or inflammation, and some cases of inability to move the limbs. Method explisit instruction health education is one of the firt aids in sprain. The research to determine of effect method explisit instruction health education on the attitude first aids futsal sport in STIKes hutama abdi husada tulungagung.This study design is a pre experiement with the pre – post test design with the population is a member of the futsal sport in STIKes Hutama Abdi Husada Tulungagung. Study found that the attitudes of members of futsal before being given health education, most respondents were 23 respondents (57.5%) had a negative attitude. And after being given health education mostly of the respondents, as many as 28 respondents (70%) have a positive attitude. Based on Wilcoxon statistical test results obtained p 0.000 <α 0.05 so that H0 is rejected, which means there is an influence of health education explicit instruction method on the attitude of first aid sprain. Study after the health education method explicit instruction about first aid sprain there is an increase in the attitude of members of UKM futsal . This research can be used as one of the sources of information expected by members of UKM futsal  to be able to apply the first aid sprain attitude that has been given by health workers and to find out the actions when someone experiences a sprain.